The empirical core-chain model - Hammouda, Boualem; Kim, Man-Ho (ELSEVIER SCIENCE BV, 2017)
Small-angle scattering requires models to analyze the data. A core-chain model has been available to fit data from solutions of core-chain particles. When the core particles are "hard" with well-defined surface, that model has been found to work well and produce characteristic oscillations observed in the data. In the case of "soft" core particles with no well-defined surface and no distinct oscillations in the data, an empirical core-chain model is introduced here. This model includes chain swelling in the grafted polymer chains. It was used to fit small-angle neutron scattering (SANS) data from a dilute solution of core-chain particles in which the core is "soft". The smooth data trends (no oscillations) are nicely reproduced. Moreover, the radius of gyration of core-chain particles has been worked out and estimated for the measured sample. Published by Elsevier B.V.
Keywords: X-RAY-SCATTERING; INDUCED AGGREGATION; POLYMER MIXTURES; ANGLE; SANS; MAGNETOTRANSPORT; MICROSTRUCTURE; CONFORMATION; TRANSITIONS; MORPHOLOGY